Implementasi Strategi Komunikasi QRIS TAP sebagai Inovasi Baru Sistem Pembayaran Digital Melalui Media Sosial Bank Indonesia - Hasna Abidah Zain; Sri Hastjarjo (Universitas Sebelas Maret (UNS), 2026)
In an effort to accelerate national financial inclusion, Bank Indonesia continues to promote innovation in digital payment systems, one of which is the launch of the QRIS Tap feature based on Near Field Communication (NFC) technology in March 2025. Despite offering convenience, speed, and efficiency, the adoption of QRIS Tap remains limited, necessitating effective communication strategies to achieve broader public acceptance. Social media has been chosen as the primary communication channel due to its ability to reach digital audiences in an interactive and participatory manner. This study aims to analyze the implementation of Bank Indonesia’s communication strategy in promoting QRIS Tap through its official social media accounts. Using a qualitative approach with a single case study design, data were collected through in-depth interviews and content documentation analysis of social media posts from March to June 2025. Data validity was ensured using triangulation techniques, and the analysis was conducted through an explanation-building approach. The findings indicate that the communication strategy focuses on the early stages of innovation diffusion, namely awareness, interest, and information seeking. The communication content selectively highlights innovation characteristics such as relative advantage, compatibility, and ease of use. However, aspects such as trialability and observability are still lacking due to infrastructure limitations and a scarcity of user experience-based content. Moreover, efforts to drive action and experience sharing remain minimal due to the gradual communication approach and the underutilization of testimonial-based content production. This study concludes that the implemented communication strategy aligns with the initial stages of innovation diffusion but needs to be strengthened in terms of calls to action and social validation to foster broader adoption.